A centrally-controlled intelligent protection switching scheme for WDM-PONs - Zhong, Wende (2013)
Several protection schemes have been proposed for wavelength division multiplexed passive optical networks (WDM-PONs). However these schemes only work under the assumption that all the optical network units (ONUs) and the optical light terminal (OLT) continuously transmit optical signals. In practice, some ONUs may be in sleep mode to save power consumption or may be shut down whenever users are offline. Under such scenarios, the existing schemes would not work. To deal with more practical operation scenarios, we propose a centrally controlled intelligent protection switching scheme for survivable WDM-PONs. It provides 1:1 downstream protection and 1+1 upstream protection capabilities. A novel logic decision unit in conjunction with a power monitoring unit is implemented in the OLT to enable the intelligent protection switching in more practical operation scenarios. Moreover, by monitoring the optical power of each channel on both working and protection paths, our proposed protection scheme can tell the connection status of every fiber path, thus facilitating a faster failure recovery. The scheme feasibility is experimentally verified with 10 Gbit/s downstream and 1.25 Gbit/s upstream transmissions.